An Intelligent Pruning Device for Tomato Lateral Branches. Issue 3 (January 2021) - Sun, Wei; Cao, Shanshan; Qiu, Qin; Wu, Jianzhai; Xing, Liwei; Liu, Jifang
Abstract: In order to realize automatic pruning technology of tomato, an intelligent pruning device of tomato lateral branch was designed. A pulley is arranged in the track at the top of the greenhouse tomato planting shed, and a bracket is arranged through a mechanical connection, and a positioning module and a lidar module, a positioning module, a lidar module, a secondary close-range camera and a binocular camera are arranged in the middle section of the crossbar. Through binocular camera to identify and locate the axil part of the leaf, the mechanical arm II fixed the main stem of tomato plant, and judged whether the lateral branch grew in the axil of the leaf through the terminal visual unit, so as to prune or smear the inhibitor to complete the pruning of the tomato lateral branch. This paper effectively solves the efficiency of tomato daily management low and low precision technical problems, which provide a solution for the artificial picking of substitute tomatoes.